2008
DOI: 10.1101/gad.471708
|View full text |Cite
|
Sign up to set email alerts
|

Trim11 modulates the function of neurogenic transcription factor Pax6 through ubiquitin–proteosome system

Abstract: [Keywords: Cortex; neurogenesis; Pax6; ubiquitin-proteosome system] Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 52 publications
2
93
0
Order By: Relevance
“…Intriguingly, the elimination of Pax6 function after the generation of IGL neurons did not affect either the specification or the number of the resulting SGL neuronal lineages. During the progression of neuronal differentiation, Pax6 expression strongly declines after E14.5 at both the transcriptional and translational level (Tuoc and Stoykova, 2008b). Together, these findings suggest that the low level of Pax6 in late RGPs does not play an important role in the specification of SGL versus IGL neuronal fate.…”
Section: Absence Of Pax6 Causes Sgl Dysgenesis But Does Not Affect Thsupporting
confidence: 53%
“…Intriguingly, the elimination of Pax6 function after the generation of IGL neurons did not affect either the specification or the number of the resulting SGL neuronal lineages. During the progression of neuronal differentiation, Pax6 expression strongly declines after E14.5 at both the transcriptional and translational level (Tuoc and Stoykova, 2008b). Together, these findings suggest that the low level of Pax6 in late RGPs does not play an important role in the specification of SGL versus IGL neuronal fate.…”
Section: Absence Of Pax6 Causes Sgl Dysgenesis But Does Not Affect Thsupporting
confidence: 53%
“…50,51 The following polyclonal (pAb) and monoclonal (mAb) primary antibodies used in this study were obtained from the indicated commercial sources: Brg1 rabbit pAb (Santa Cruz), Brg1 mouse mAb (Santa Cruz), Brm mouse mAb (BD Biosciences), Brm rabbit pAb (Abcam), BAF250 mouse mAb (Sigma), BAF170 rabbit pAb (Bethyl), BAF170 rabbit pAb (Sigma), BAF155 rabbit pAb (Santa Cruz), BAF155 mouse mAb (Santa Cruz), BAF60a mouse mAb (BD Biosciences), GAPDH rabbit pAb (Santa Cruz), ß-actin rabbit pAb (Sigma), and H3K27me3 rabbit pAb (Upstate). The utilized secondary antibodies included peroxidase-conjugated goat anti-rabbit IgG (1:10,000; Covance), peroxidase-conjugated goat anti-mouse IgG (1:5000; Covance), and Alexa 488-or Alexa 568-conjugated IgG (various species,1: 400; Molecular Probes).…”
Section: Immunohistochemistry (Ihc) and Western Blotting (Wb)mentioning
confidence: 99%
“…Densitometric quantification of WB bands and quantitative analysis of IHC signal intensities were performed using the ImageJ software, as described previously. 21,51 Statistical analyses were carried out using the Student's t-test. The results are presented as the mean § SEM.…”
Section: Imaging and Quantitative And Statistical Analysesmentioning
confidence: 99%
“…These isoforms vary from each other in their Nterminal structures. The common p46 isoform has a 128-amino acid PD at the N terminus and a 56-amino acid HD in the central region which bind specifically to different DNA sequences, P6CON and P3 (TAAT/ATTA), respectively (12)(13)(14). At the C terminus, a conserved domain rich in proline (P), serine (S), and threonine (T) residues exists in all Pax-6 isoforms and thus is named the "PST" domain ( Fig.…”
mentioning
confidence: 99%